Dynamic organelle localization and cytoskeletal reorganization during preimplantation mouse embryo development revealed by live imaging of genetically encoded fluorescent fusion proteins - Kiyonari, Hiroshi (Genesis, 2019)
Live imaging is one of the most powerful technologies for studying the behaviors of cells and molecules in living embryos. Previously, we established a series of reporter mouse lines in which specific organelles are labeled with various fluorescent proteins. In this study, we examined the localizations of fluorescent signals during preimplantation development of these mouse lines, as well as a newly established one, by time‐lapse imaging. Each organelle was specifically marked with fluorescent fusion proteins; fluorescent signals were clearly visible during the whole period of time‐lapse observation, and the expression of the reporters did not affect embryonic development. We found that some organelles dramatically change their sub‐cellular distributions during preimplantation stages. In addition, by crossing mouse lines carrying reporters of two distinct colors, we could simultaneously visualize two types of organelles. These results confirm that our reporter mouse lines can be valuable genetic tools for live imaging of embryonic development.